Pengaruh Bonus Demografi Dan Tingkat Pengangguran Terbuka Terhadap Pertumbuhan Ekonomi Di Provinsi Lampung Periode 2014-2023 - Gea Anisa Kusuma Ananda; Nur Huda; Mila Marlina; Muhammad Kurniawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Economic growth is an indicator of development success. Therefore, the higher the economic growth, the higher the welfare of the community. The success or failure of regional development depends on several indicators, including economic growth which reflects the growth of regional gross domestic product (GDP). In this research, we will examine the influence of the demographic bonus and Open Unemployment Rate on Economic Growth for the 2014-2023 Period. The data used in this research is secondary data, namely data obtained from a second source during the period 2014 to 2023. The type of data used in this research is time series data, namely time series data. Based on the research results, it shows that the independent variables influence Economic Growth (PE) in Lampung Province. Meanwhile, partially, the Demographic Bonus (BD) and Open Unemployment Rate (TPT) variables do not have a positive effect on Economic Growth (PE) in Lampung Province. BD and TPT together influence Economic Growth (PE) in Lampung Province in 2013-2022, using a confidence level of 95% or with an alpha (ɑ) of 0.05.